The Role Of Good Corporate Governance In Moderating The Effect Of Green Accounting On Tax Avoidance In IDXQ30 For The 2022-2024 Period (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This research analyzes the impact of green accounting on tax avoidance and the moderating role of corporate governance, specifically institutional ownership and independent commissioners, among IDXQ30 companies on the Indonesia Stock Exchange (2022–2024). Although tax avoidance is a legal activity, it carries the potential to diminish state revenue, which is essential for funding national development and enhancing public welfare. While the adoption of green accounting is intended to improve corporate transparency and accountability, there is a possibility that it may still be utilized as a tool for tax planning in practical applications. Consequently, robust corporate governance mechanisms are required to guarantee that the implementation of green accounting remains consistent with sustainability goals and regulatory standards. This study adopts a quantitative approach through the application of a causal-comparative method. Necessary secondary data were collected from annual reports and sustainability reports of companies. Green accounting is quantified using the environmental cost ratio, tax avoidance is assessed through the Effective Tax Rate (ETR), and both institutional ownership and independent commissioners serve as the moderating variables. Data analysis is performed through multiple linear regression. This study aims to provide empirical evidence on how corporate governance strengthens the relationship between green accounting and tax avoidance, specifically within companies that possess high liquidity and strong governance profiles, such as those categorized in the IDXQ30 index.
Keywords: Akuntansi Hijau, Kepemilikan Institusional, Dewan Komisaris Independen, Penghindaran Pajak